Nanomolar Benzothiazole-Based Inhibitors of 17β-HSD10 with Cellular Bioactivity - Hanzlova, Michaela; Miskerikova, Marketa Sedlacek; Rotterova, Aneta; Chalupova, Katarina; Jurkova, Katarina; Hamsikova, Marie; Andrys, Rudolf; Haleckova, Annamaria; Svobodova, Jana; Schmidt, Monika; Benek, Ondrej; Musilek, Kamil (ACS medicinal chemistry letters, 2023)
Multifunctional mitochondrial enzyme 17β-hydroxysteroid dehydrogenase type 10 (17β-HSD10) is a potential drug target for the treatment of various pathologies. The most discussed is the pathology associated with Alzheimer's disease (AD), where 17β-HSD10 overexpression and its interaction with amyloid-β peptide contribute to mitochondrial dysfunction and neuronal stress. In this work, a series of new benzothiazole-derived 17β-HSD10 inhibitors were designed based on the structure-activity relationship analysis of formerly published inhibitors. A set of enzyme-based and cell-based methods were used to evaluate the inhibitory potency of new compounds, their interaction with the enzyme, and their cytotoxicity. Most compounds exhibited significantly a higher inhibitory potential compared to published benzothiazolyl ureas and good target engagement in a cellular environment accompanied by low cytotoxicity. The best hits displayed mixed-type inhibition with half maximal inhibitory concentration (IC50) values in the nanomolar range for the purified enzyme (3-7, 15) and/or low micromolar IC50 values in the cell-based assay (6, 13-16).